Cytological differentiation and cell wall involvement in the growth mechanisms of articulated laticifers in Tabernaemontana catharinensis A.DC. (Apocynaceae) - Canaveze, Yve [UNESP]; Mastroberti, Alexandra Antunes; Mariath, Jorge Ernesto De Araujo; Machado, Silvia Rodrigues [UNESP] (Springer Nature, 2018)
The cellular mechanisms of laticifer growth are of particular interest in plant biology but are commonly neglected. Using transmission electron microscopy and immunocytochemical methods, we recorded cytological differentiation and evaluated the cell wall involvement in the growth of articulated laticifers with intrusive growth in the mature embryo and plant shoot apex of Tabernaemontana catharinensis. The incorporation of adjacent meristematic cells into the laticifer system occurred in the embryo and plant shoot apex, and the incorporated cells acquired features of laticifer, confirming the laticifers’ action-inducing mechanism. In the embryo, this was the main growth mechanism, and began with enlargement of the plasmodesmata and the formation of pores between laticifers and meristematic cells. In the plant shoot apex, it began with loose and disassembled walls and the reorientation of the cortical microtubules of the incorporated cell. Plasmodesmata were absent in these laticifers. There was stronger evidence of intrusive growth in undifferentiated portions of the plant shoot apex than in the embryo. The numerous plasmodesmata in laticifers of the embryo may have been related to the lower frequency of intrusive growth. Intrusive growth was associated with presence of arabinan (increasing wall flexibility and fluidity), and absence of galactan (avoiding wall stiffness), and callose (as a consequence of reduction in symplastic connections) in the laticifer walls. The abundance of low de-methyl-esterified homogalacturonan in the middle lamella and corners may reestablish cell-cell bonding in the laticifers. The cell wall features differed between embryo and plant shoot apex and are directly associated to laticifer growth mechanisms.
Keywords: Immunocytochemistry; Intrusive growth; Laticifer system; Laticifers’ action-inducing mechanism; Ultrastructure